(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Nonalcoholic fatty liver disease (NAFLD) has been reported to have effects on kidney diseases; however, a link between NAFLD and urinary calculi remains to be confirmed. This study was conducted on a male population based on our previous Fangchenggang Area Male Health and Examination Survey in Guangxi, China in order to estimate the frequency of urinary calculi and assess the association between NAFLD and urinary calculi while controlling for possible confounders. Materials and Methods. This was a population-based cross-sectional study conducted in the Fangchenggang region in Guangxi, China. The diagnoses of NAFLD and urinary calculi were made by ultrasonography. Clinical and laboratory findings were analyzed to investigate whether NAFLD was a risk factor for urinary calculi. Results. A total of 3719 men were enrolled (age range, 17 to 88 years). Slightly more than a quarter (26.5%) of the participants were diagnosed with NAFLD. The percentage of urinary calculi in all participants was 6.9%, and the percentage of NAFLD patients with urinary calculi (8.4%) was significantly higher than that among patients without NAFLD (6.4%, P < .05). Advanced age; high body mass index; elevated levels of blood glucose, cholesterol, triglycerides, and low-density lipoprotein cholesterol; low education; lower or higher physical activity; and NAFLD were independent risk factors for urinary calculi (P < .05). Conclusions. Our results showed that NAFLD was associated with a higher incidence of urinary calculi in this cohort and NAFLD might represent a risk factor for urinary calculi.